THE CORRELATION OF MOTIVATION AND EDUCATION WITH PREGNANT WOMEN CLASS PARTICIPATION - Dwi Kurnia Purnama Sari Sari; Aris Puji Utami Utami (International Journal of Midwifery Research, 2021)
Pregnant Women Class is a study group for pregnant women with a gestational age of 4 weeks to 36 weeks (before delivery) with a maximum number of 10 participants. The research was an analytic with a cross-sectional approach. The time this research began was in September 2020 at the Puskesmas Klotok, Tuban. The population in this study were all pregnant women, who visited the Puskesmas Klotok Tuban in 2020. The sampling technique used in this study was total sampling. Secondary data from the attendance list and primary data by giving questionnaires to respondents. The independent variables in this study were motivation and education with each nominal scale and the dependent variable in this study was pregnancy class with an ordinal data scale. Data analysis in this study used Contingency Coefficient with the help of SPSS. Significant limitation if p-value < 0.05. The analysis using the Contingency Coefeccient statistical test obtained p-value = 0,017, because the p-value < 0.05 which indicates there is no correlation between gestational age and the incidence of anemia in pregnant women. The analysis using the Contingency Coefficient statistical test obtained p-value = 0,000 because the p-value <0.05 which indicates there is a correlation between motivation and participation of pregnant women attending classes for pregnant women class. Health workers are expected to increase their duties and responsibilities by providing health services as much as possible as a driving factor and strengthening the formation of positive motivation in the community